2016
DOI: 10.1038/srep28171
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induction targeting mTORC1 enhances Mycobacterium tuberculosis replication in HIV co-infected human macrophages

Abstract: To survive and replicate in macrophages Mycobacterium tuberculosis (Mtb) has developed strategies to subvert host defence mechanisms, including autophagy. Autophagy induction has the potential to clear Mtb, but little is known about its effect during controlled tuberculosis and HIV co-infection. Mammalian target of rapamycin complex1 (mTORC1) inhibitors were used to induce autophagy in human macrophages pre-infected with HIV-1BaL and infected with a low dose of Mtb (co-infected), or single Mtb infected (single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 53 publications
3
44
0
Order By: Relevance
“…However, the differences in bacterial burden tend to be less than 2.5 fold[41,44,103,104]. In addition, a recent study found that in macrophages coinfected with HIV and M. tuberculosis , stimulation of autophagy with rapamycin actually led to increased M. tuberculosis survival[106]. Thus, it will be critical to determine the impact of comorbidities such as HIV when perusing options for clinical intervention.…”
Section: Targeting Autophagy As a Host-directed Therapy To Treat Bactmentioning
confidence: 99%
“…However, the differences in bacterial burden tend to be less than 2.5 fold[41,44,103,104]. In addition, a recent study found that in macrophages coinfected with HIV and M. tuberculosis , stimulation of autophagy with rapamycin actually led to increased M. tuberculosis survival[106]. Thus, it will be critical to determine the impact of comorbidities such as HIV when perusing options for clinical intervention.…”
Section: Targeting Autophagy As a Host-directed Therapy To Treat Bactmentioning
confidence: 99%
“…For GFP-expressing M. tuberculosis the medium was supplemented with 20 µg/mL of kanamycin, and for luciferase-expressing M. tuberculosis 100 µg/mL of hygromycin was used. For infection, the bacteria were prepared as previously described [28].…”
Section: Isolation Of Neutrophils and Induction Of Apoptosismentioning
confidence: 99%
“…Macrophages were infected with 0.06 ng/mL HIV-1BaL (Lot p4238), produced as previously described [28], for 1 week prior to M. tuberculosis infection at MOI = 1-5. After M. tuberculosis infection the macrophages were incubated with apoptotic neutrophils (1: 2) for different time points, depending on the experiment.…”
Section: Hiv and M Tuberculosis Coinfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is generally believed to be host beneficial and leads to a decrease of Mtb burden in mice [94,191], but pharmacological induction of autophagy has also been shown to facilitate bacterial growth inside macrophage infected with a low burden of Mtb [192].…”
Section: Phagolysosomal Maturation Phagolysosomal Maturation Phagolysmentioning
confidence: 99%